Who will feed China? : wake-up call for a small planet - Brown, Lester Russell, 1934- (Worldwatch environmental alert series, 1995)
To feed its 1.2 billion people, China may soon have to import so much grain that this action could trigger unprecedented rises in world food prices. In Who Will Feed China: Wake-up Call for a Small Planet, Lester Brown shows that even as water becomes more scarce in a land where 80 percent of the grain crop is irrigated, as per-acre yield gains are erased by the loss of cropland to industrialization, and as food production stagnates, China still increases its population by the equivalent of a new Beijing each year.